Zinc contamination is an underestimated risk to amphibians: toxicity evaluation in tadpoles of Fejervarya limnocharis - Patar, Arabinda; Das, Indranil; Giri, Sarbani; Giri, Anirudha (Journal of Environmental Engineering and Landscape Management, 2021)
Aquatic environments are often contaminated with zinc. Amphibian tadpoles are likely to be exposed to high concentrations of zinc present in these environments. We determined the acute and sub-chronic toxicity of ZnCl2 on Fejervarya limnocharis tadpoles under laboratory conditions. The LC50 values of ZnCl2 were found to be 5.81, 4.32, 3.79 and 3.61 mg/L at 24, 48, 72 and 96 h of exposure respectively. Long-term exposure to sub-lethal concentrations of ZnCl2 induced significant mortality in concentration and time dependent manner. Sub-lethal ZnCl2 exposure significantly altered survival, body length and body weight at metamorphosis. Micronucleus test and comet assay indicated the genotoxic potential of ZnCl2. Significant increase in DNA strand break was observed following ZnCl2 exposure equivalent to 1% of the of 24 h LC50 value. The findings indicate possible adverse to tadpoles inhabiting aquatic environments contaminated with zinc. In addition, the findings may be extrapolated to aquatic organisms of similar torphic status.